Using memes to promote student engagement and classroom community during remote learning. Issue 2 (7th December 2022) - Tu, Kevin; Sun, Angela; Levin, Daniel M.
Abstract: As colleges moved to online teaching during the COVID‐19 pandemic, many instructors found it difficult to maintain student engagement and classroom community in the virtual environment. We developed a semester‐long activity for a molecular biology research methodology course where students created, and shared original memes related to course content with peers through group chat. Surveys and semi‐structured interviews revealed that the exercise was effective in promoting student engagement, a sense of community, and relieving stress.